Numerical analysis of kraft paper honey comb subjected to uniform compression loading - Abd Kadir, Nurdina; Aminanda, Yulfian; Shaik Dawood, Mohd Sultan Ibrahim; Mokhtar, Hanan (IOP publisher, 2017)
The objective of this study is to investigate the crushing strength of Kraft paper honeycomb with different thickness of cell wall and different cell size subjected to compression loading. At first, experimental tests were carried out on Kraft paper honeycomb with 10mm cell size and 0.6mm thickness of paper with different mass density (RO). Then, a finite element model was developed in order to study the effect of cell size and thickness of cell wall on crushing properties of Kraft paper honeycomb. Based on the simulation results, the cell size and thickness of cell wall of Kraft paper honeycomb influence the crushing properties of the honeycomb. Crushing strength increases with decreasing the cell size which for the range of the study, cell size 10mm shows the highest strength. Meanwhile, 0.4mm thickness of cell wall results the higher crushing strength of honeycomb. Also, higher density gives higher crushing strength where in this study is found for 2.236x 106 kg/mm3.